Leaking Space. - MITCHELL, NEIL (Communications of the ACM, 2013)
The article discusses space leaks, which is when a computer program uses more of the computer's memory than is necessary. The control of a computer program's evaluation to reduce the time between allocating and discarding memory to eliminate space leaks is discussed. Lazy evaluations, when an evaluation of an expressing is delayed until its value is needed, and closures, a function combined with its environment are both considered as a cause of space leaks and attributed to lazy functional programming languages.